2021
DOI: 10.24191/ajue.v17i4.16225
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction in Using a Learning Management System (LMS) for Blended Learning Courses for Tertiary Education

Abstract: This study aims to investigate factors associated with students’ satisfaction with using LMS - UNIEC Virtual in blended learning courses in UNITAR International University, Kelana Jaya. Three factors; perceived ease of use (PEOU), facilitating conditions, and interaction are selected as independent variables in this study. This research was designed using a quantitative method with 17 closed-ended items questions with a 5-Likert scale and one open-ended question. The questionnaire was developed and modified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…A study by Ikhsan et al (2023) found that perceived ease of use had a significant impact on students' satisfaction with LMS. Similarly, Nasir et al (2021) reported that the ease of use of the LMS was a crucial factor affecting students' satisfaction with the system. A system that is easy to navigate will increase the frequency of use amongst its users and while helping them to be more skilful in fully utilizing its functions and features.…”
Section: Perceived Usefulnessmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by Ikhsan et al (2023) found that perceived ease of use had a significant impact on students' satisfaction with LMS. Similarly, Nasir et al (2021) reported that the ease of use of the LMS was a crucial factor affecting students' satisfaction with the system. A system that is easy to navigate will increase the frequency of use amongst its users and while helping them to be more skilful in fully utilizing its functions and features.…”
Section: Perceived Usefulnessmentioning
confidence: 98%
“…This includes the use of LMS as a platform to interact with the instructors and fellow students. Such integrated communication platform is useful as it encourages students to interact with the instructors and their classmates pertaining to their studies (Nasir et al, 2021). Students are no longer required to book appointments for a face-to-face consultation with their instructors at an SF SQ PU PEOU allocated time.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…The results indicate that LMS quality can be improved by making it more usable to students. Usability can be enhanced through access, ease of use provided to students, and whether the system has sufficient features to increase student engagement and interaction (Nasir et al, 2021) [63].…”
Section: Main Analysismentioning
confidence: 99%
“…In any case, positive student feedback encourages to continue the development of e-education from the perspective of preparing experts in medicine and psychology (teaching clinical and special psychology) as an attractive educational option (Sindiani et al, 2020). In this regard, it can be said that an LMS focused on blended learning can effectively support e-learning environments in universities (Mohd Nasir et al, 2021). In addition, the use of virtual simulators can be a decisive argument in favor of online technologies for teaching medical specialties and developing not only theoretical knowledge but also practical skills (Dammerer et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%